Hiding the guillotine : public executions in France, 1870-1939 - Taïeb, Emmanuel (Cornell University Press, 2020)
"This book explores the evolution of public executions in France: the public dimension of the death penalty, its ritual and theatrical form, its attendance, and the continuous critics of this power technology"--